في قراءة الكلمة العربية لدى الأطفال 10 سنوات (fonologis) تحليل الأخطاء الفنولوجية - Nada, Qatrun; Hasyim, Syarifuddin; Hayati, Salma (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2020)
The purpose of this study was to analyze phonological errors by children in the Arabic vocabulary reading. This study involved five children at the age of ten years old as the subjects. The content-analysis method was used to analyze the vocabularies fromprepared recording. Futhermore, the data were analyzed by using the triangulation theory from Miles and Huberman. The results informed that the phonological errors generally occur on several hijaiyah pronunciation such as ث، ح، خ، ذ، ز، ص، ض، ط، ظ، ع، غ، ق.